The effectiveness of the “Predict-Explain-Enact-Observe-Reflect (PEEOR)” Instructional strategy on conceptual understanding and motivation in motion and force topic. - Amssalu Wondmagegn Getu (Utan Kayu Publishing, 2025)
This study examined the effectiveness of Predict-Explain-Enact-Observe–Reflect (PEEOR) instructional strategy on Woldia College of Teachers’ Education general science students’ conceptual understanding and motivation in motion and force topic. The pre-test posttest quasi-experimental design was used for the study. The sample constituted purposefully selected 107 general science summer, year II students of Woldia College of Teacher Education. Data was collected through conceptual understanding test and post motivation questionnaire. The conceptual understanding test is made up of 15 questions. Its KR-20 reliability value was 0.75. The Cronbach Alpha (?) reliability coefficient value of the scale was determined to be .84. Results obtained through the use of descriptive statistics and ANCOVA showed that PEEOR group (adjusted mean =6.787) was significantly different from traditional group (adjusted mean =5.134). POE group (adjusted mean =6.472) did not differ significantly from either PEEOR or traditional group. On other hand with regard to the motivation of the student, there was a statistically significant difference at the p .05 level in post test motivational questionnaire (PMQ) scores for the three groups F(2, 104) = 4.753, p=.011. Consequently, it was recommended that college physics teachers should adopt the Predict-Explain-Enact-Observe-Reflection instruction strategy while the college and department head of natural science should propagate the potentials inherent in the novel strategy among science teachers.